The potential use of legitimate force for the preservation of order - Arnež, Jasmina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2016)
In the UK, private policing institutions have been rapidly increasing since the 1980s, so the lines between public- and private police have been blurred. This paper explores whether there is a policing function that is inherent in public police and if so, why it occupies this position. It integrates Rousseau's social contract theory, Bittner's definition of police functions, Brodeur's reasoning on force and Loader and Walker's concept of "policing as public good" to argue that the potential use of legitimate force for the preservation of order is the function intrinsic to public police. It shows why it cannot and should not be carried out by private police and outlines how it depends on police legitimacy. It concludes with an abstract rethinking of public-state-police relations to determine that this function remains in the realm of public policing.
Keywords: Velika Britanija; policija; pooblastila; pristojnosti; zasebna podjetja